Visual evoked potentials in the horse. Issue 1 (December 2016) - Ström, L.; Ekesten, B.
Abstract Background Electrical potentials generated in the central nervous system in response to brief visual stimuli, flash visual evoked potentials (FVEPs), can be recorded non-invasively over the occipital cortex. FVEPs are used clinically in human medicine and also experimentally in a number of animal species, but the method has not yet been evaluated in the horse. The method would potentially allow the ophthalmologist and equine clinician to evaluate visual impairment caused by disorders affecting post-retinal visual pathways. The aim was to establish a method for recording of FVEPs in horses in a clinical setting and to evaluate the waveform morphology in the normal horse. Methods Ten horses were sedated with a continuous detomidine infusion. Responses were recorded from electrodes placed on the scalp. Several positions were evaluated to determine suitable electrode placement. Flash electroretinograms (FERGs) were recorded simultaneously. To evaluate potential contamination of the FVEP from retinal potentials, a retrobulbar nerve block was performed in two horses and transection of the optic nerve was performed in one horse as a terminal procedure. Results A series of positive (P) and negative (N) peaks in response to light stimuli was recorded in all horses. Reproducible wavelets with mean times-to-peaks of 26 (N1), 55 (P2), 141 (N2) and 216 ms (P4) were seen in all horses in all recordings. Reproducible results were obtained when the active electrode was placed in the midline rostral to the nuchal crest. Recording at lateral positions gave more variable results, possibly due to ear muscle artifacts. Averaging ≥100 responses reduced the impact of noise and artifacts. FVEPs were reproducible in the same horse during the same recording session and between sessions, but were more variable between horses. Retrobulbar nerve block caused a transient loss of the VEP whereas transection of the optic nerve caused an irreversible loss. Conclusions We describe the waveform of the equine FVEP and our results show that it is possible to record FVEPs in sedated horses in a clinical setting. The potentials recorded were shown to be of post-retinal origin. Further studies are needed to provide normative data and assess potential clinical use.